Effects of Angle and Rate of Twist via Pre-Torsional Deformation on Tensile Properties and Hardness of Hot-Rolled, Low-Alloy Steel Rods - Jantasorn, Pawat; Thamma, Ukrit (Trends in Sciences, 2022)
The effects of twist angle and twist rate during the pre-torsional deformation on tensile and hardness properties of hot-rolled SCM415 low-alloy steel were investigated. Hot-rolled SCM415 round tensile specimens were pre-torsioned using a free-end torsion machine to 36, 72, 144 and 288 degrees at 2 different twist rates of 0.1 and 30 rpm. As the angle and the rate of twist increased, yield strength and ultimate tensile strength increased with a tradeoff in a reduction in ductility. The relationship of true stress and true strain within the uniform plastic deformation were well described by a power law. The strength coefficient and strain hardening exponent obtained from the power-law curve fitting decreased with increasing twist angle and higher twist rate, suggesting that higher shear strain and shear strain rate led to a decrease in work hardening capacity. The local hardness after pre-torsional deformation showed a positive gradient from specimens’ centers to their surfaces along the radial direction. Also, the local hardness at the same radial position increased with the increasing angle and rate of twist. The average grain sizes were uniform along the radial direction and were comparable for all pre-torsional conditions. The strengthening mechanism via pre-torsional deformation of hot-rolled SCM415 was shown to be dominated by the strain hardening effect. HIGHLIGHTS The effects of twist angle and twist rate during the pre-torsional deformation using a free-end torsion tester on tensile and hardness properties of hot-rolled SCM415 low-alloy steel were investigated Within uniform plastic deformation region, the power-law parameters, namely strength coefficient (K) and strain hardening exponent (n) decreased with increasing amount of shear plastic strain and shear strain rate during the pre-torsional deformation Local Vicker hardness showed a positive gradient from the central region to the surface of pre-torsioned specimens, and the local hardness at the same distance from the center increased with increasing torsional angle and twist rate The average grain sizes of pre-torsioned specimens were found to be unaffected by the amount of torsional angle or the rate of twist The strengthening of hot-rolled SCM415 steel via pre-torsional deformation is predominated by strain hardening effect GRAPHICAL ABSTRACT